Molecular characterisation and antibiotic sensitivity profile of Pasteurella multocida isolated from poultry farms in Malaysia - Sabsabi, Mohammad A. Sabsabi; Zakaria, Zunita; Abu, Jalila; Nik M. Faiza (Facultad de Ciencias Veterinarias,Universidad Austral de Chile, 2021)
Fowl cholera has caused significant economic losses in many poultry producing countries worldwide. In Malaysia, outbreaks of fowl cholera are frequently reported and encountered in different types of poultry productions. The objective of this study was to characterise 13 avian Pasteurella multocida, isolated from fowl cholera outbreaks in Central Peninsular Malaysia in the period between 2000 and 2018. The isolates were subjected to multiplex polymerase chain reaction (PCR) for capsular serotyping, disc diffusion method for antimicrobial susceptibility profiles, and molecular genotyping using pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). The capsular serotyping showed all 13 Pasteurella multocida isolates belonging to capsular serotype A. The antimicrobial susceptibility showed several multidrug resistance strains among the P. multocida isolates. All the isolates were resistant to erythromycin (100%), streptomycin (68%), tetracycline (37%), enrofloxacin (37%), florfenicol (23%), penicillin G (14%), gentamicin (14%), and amoxicillin (14%). The PFGE analysis clustered the isolates into three clones. Group A included isolates with a similarity of 87% from the year 2000, 2013, and 2018. Three sequence types were identified using MLST typing namely, ST129, ST231, and ST355. The ST355 was assigned for the first time in the Rural Industries Research and Development Corporation (RIRDC) database. Besides, ST129 has been reported in India, China, and Sri Lanka, which highlights the possibility of transmission between Asian countries. This study provides an insight into epidemiological information of Pasteurella multocida that causes fowl cholera outbreaks in the central region of Peninsular Malaysia.